Rupiah Stability Dominates Indonesian Consumer Expectations Dynamics - Saputra, Khrisna; Setiawati, Ririt Iriani Sri (Academia Open, 2026)
General Background Public expectations are central to macroeconomic stability because they are linked to consumption, savings, and investment behavior. Specific Background In Indonesia, the Consumer Expectations Index reflects public perceptions of future economic conditions, while the exchange rate and BI-7 Day Reverse Repo Rate represent key monetary variables during the 2016–2025 period of global shocks and domestic uncertainty. Knowledge Gap Previous studies have examined exchange rates and interest rates in relation to macroeconomic indicators, but limited research has focused on their role in public expectations, particularly in Indonesia during the post-pandemic period. Aims This study analyzes the relationship between the exchange rate, BI-7 Day Reverse Repo Rate, and Consumer Expectations Index using secondary time series data from Bank Indonesia. Results The Vector Error Correction Model confirms cointegration among all variables, indicating a long-term equilibrium relationship. The exchange rate is statistically significant in both the short and long run, whereas the BI-7 Day Reverse Repo Rate remains insignificant. Granger causality shows a one-way relationship from the Consumer Expectations Index to the BI-7 Day Reverse Repo Rate, and FEVD results indicate that exchange rate contribution is greater than the benchmark rate. Novelty This study provides empirical evidence that Rupiah exchange rate movement is more persistent than interest rate policy in explaining expectation formation. Implications The findings suggest that maintaining exchange rate stability is crucial for supporting public confidence and monetary policy responsiveness in Indonesia. Highlights: Exchange rate movements were statistically significant across short and long horizons. BI7DRR showed no significant relationship with CEI in VECM estimation. One-way causality ran from CEI toward BI7DRR. Keywords: Exchange Rate, BI-7 Day Reverse Repo Rate, Consumer Expectations Index, VECM